2000
DOI: 10.1006/mthe.2000.0107
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Nonviral Cutaneous Transfection

Abstract: Preclinical in vivo rodent, porcine, and primate experiments aimed at enhancing nonviral transgene delivery to skin have been performed. These investigations have identified a compound (aurintricarboxylic acid or ATA) that enhances transfection activity of "naked" plasmid and pulsed electrical fields (electroporation or EP) that synergistically boosts transgene expression to an average of 115-fold more than that observed with free DNA (P < 0.00009). When plasmid is intradermally injected with or without ATA, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 20 publications
3
65
0
1
Order By: Relevance
“…The studies on the application of electroporation-mediated gene transfer to larger animals are ongoing. 39,40 Recently, it has been reported that local gene transfer could result in a systemic therapeutic effect without systemic elevation of the therapeutic protein. 19,41 Further investigation on the mechanism responsible for these phenomena may help to develop the clinically relevant protocol for electroporation-based gene delivery strategy for the treatment of human RA.…”
Section: Discussionmentioning
confidence: 99%
“…The studies on the application of electroporation-mediated gene transfer to larger animals are ongoing. 39,40 Recently, it has been reported that local gene transfer could result in a systemic therapeutic effect without systemic elevation of the therapeutic protein. 19,41 Further investigation on the mechanism responsible for these phenomena may help to develop the clinically relevant protocol for electroporation-based gene delivery strategy for the treatment of human RA.…”
Section: Discussionmentioning
confidence: 99%
“…For electroporation gene delivery to skin, plasmid DNA may be injected intradermally [1][2][3][4][5][6][7][8][9][10] or biolistically. 11 Pulses are applied to the skin surface or through penetrating (needle) electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive electrodes used in cutaneous gene delivery include 2-needle, 5 6-needle, 12 and 7-pin arrays. 2,3 Comparisons show that penetrating electrodes induce higher levels of transgene expression, 2,3,5 but these electrodes raise the specter of needle insertion. Previous studies have also shown that delivery is more efficient when the field is applied in more than one direction.…”
Section: Introductionmentioning
confidence: 99%
“…Its advantages, compared with other nonviral gene delivery systems, are that gene expression is drastically increased (2-to 4-log fold), longlasting (months), and very specific and localized . This technique has also been successful in various tissues such as skeletal muscle (Muramatsu et al, 1998;Aihara and Miyazaki, 1999;Gehl and Mir, 1999;Imai and Isaka, 1999;Mathiesen, 1999;Rizzuto et al, 1999;Bettan et al, 2000;Lemieux et al, 2000;Maruyama et al, 2000;Vicat et al, 2000;Lucas and Heller, 2001;Muramatsu et al, 2001), liver (Suzuki et al, 1998;Heller et al, 2000), testis (Muramatsu et al, 1997;Yamazaki et al, 1998;Yamazaki et al, 2000), skin (Johnson et al, 1998;Vanbever and Preat, 1999;Glasspool-Malone et al, 2000), cornea (Oshima et al, 1998;Sakamoto et al, 1999), cardiaovascular (Harrison et al, 1998;Martin et al, 2000) and mammary tumor tissue Wells et al, 2000;Lohr et al, 2001). In particular, gene delivery to skeletal muscle is a promising strategy for the systemic secretion of therapeutic proteins.…”
Section: Introductionmentioning
confidence: 99%